1993
DOI: 10.1007/bf03010102
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid embolus

Abstract: Case reportIn 1987, a 27-yr-old healthy woman presented for an elective Caesarean section. She had had a previous Caesarean section under general anaesthesia without difficulty. There were no problems found on history or physical examination. The patient decided after discussion with her general practitioner and anaesthetist to have an epidural an- Accepted for publication 25th June, 1993. aesthetic for pain control. Haemoglobin and urinalysis were normal. She was given 30 ml Na citrate outside the OR.At 08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition, leukotrienes and other arachidonic acid metabolites have been shown to have procoagulant activity (23). The mechanism of DIC may also relate to tissue damage caused by the effects of hypoxaemia and a low cardiac output (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, leukotrienes and other arachidonic acid metabolites have been shown to have procoagulant activity (23). The mechanism of DIC may also relate to tissue damage caused by the effects of hypoxaemia and a low cardiac output (21).…”
Section: Discussionmentioning
confidence: 99%
“…36 Components of the¯uid which may be demonstrated include epithelial squames shed from fetal skin, lanugo hair, vernix caseosa, mucin and bile pigments deriving from meconium, and decidual cells. The foramen ovale does not completely close after birth in 35% of the normal population and in others may re-open during the early phase of severe pulmonary hypertension which is seen during AFE.…”
Section: Diagnosismentioning
confidence: 99%
“…26 16 12 134 1.4 Cardiac index 15 43 28 14 ± 2.28 Cardiac index 16 46 18 9 156 41 17 36 13 12 ± 8.1 Cardiac Output * Normal values 13 + 5 mm Hg, mean + SD. 26 16 12 134 1.4 Cardiac index 15 43 28 14 ± 2.28 Cardiac index 16 46 18 9 156 41 17 36 13 12 ± 8.1 Cardiac Output * Normal values 13 + 5 mm Hg, mean + SD.…”
Section: Goals Of Therapymentioning
confidence: 99%
“…Most reports have documented normal-to-decreased cardiac output and normal pulmonary-artery pressure associated with pulmonary edema or the adult respiratory distress syndrome. [11][12][13] In a model involving a catheterized goat, Hankins et al 14 reported a transient marked pressor response in both the systemic and pulmonary circulations, with a minimal, brief increase in cardiac output. If the amniotic fluid contained meconium, however, the cardiac output was sharply depressed, with an even greater vascular pressor response.…”
mentioning
confidence: 99%